The Resilience of Rural Tourism and Adjustment Measures for Surviving The COVID-19 Pandemic: Evidence from Bromo Tengger Semeru National Park, Indonesia - Novi Meilana Sari; Iwan Nugroho; Evi Nurifah Julitasari; Rita Hanafie (Forestry Faculty, Universitas Hasanuddin, 2022)
The COVID-19 virus pandemic has generated an unprecedented impact on all aspects of life, including rural tourism. This study aims to study the impact of the COVID-19 pandemic on the performance of homestay businesses in Gubukklakah Village, Malang Regency, and their adjustment measures to get out of the pandemic. A survey research with descriptive and quantitative approaches was conducted on 47 active homestay owners. 98% of the respondents stated that the pandemic affected their homestay business activities. About 44.6% of them said that the pandemic would not last long, while more than 50% of them said that the pandemic would last a long time. The pandemic has decreased the number of active homestays from 47 to 11, coupled with an 81% decline in income. Due to the pandemic, about 85.1% of the respondents returned to farming activities. The study suggests several actions that can be done to respond to the pandemic, namely the application of health protocols in various activities, the provision of cash or non-cash assistance to pandemic affected families, the strengthening of the agricultural sector and skilled human resources in tourism services, and the innovation of outdoor tourism products based on local uniqueness.